LGG-27. A CASE FOR EARLY DABRAFENIB USE IN PATIENTS WITH LOW-GRADE GLIOMAS. Issue 2 (22nd June 2018) - Patel, Krupesh; Hanson, Derek
Abstract: BRAF kinase mutations and duplications are among the most common genetic alterations seen in pediatric low-grade gliomas. The BRAF V600E mutation is a missense mutation involving an amino acid substitution at position 600 in BRAF, from valine to glutamic acid, leading to constitutive activation of the MAPK pathway. Dabrafenib, a selective BRAF inhibitor, has demonstrated clinical efficacy in BRAF V600E-positive low-grade gliomas in early phase testing. While dabrafenib is typically used as a second-line agent in low-grade glioma, its efficacy, minimal toxicity, and ease of administration make the drug an attractive candidate for first-line use. We present two patients with BRAF V600E-postitive low-grade gliomas who received respective late and early dabrafenib therapy. The first is a patient with a glioneuronal tumor involving the brain and spine. Over nine years, her symptoms progressed to include paraplegia despite surgical resection, multiple chemotherapy regimens, and radiotherapy. Following her most recent progression, her tumor was re-examined and found to express the BRAF V600E mutation. She received dabrafenib with subsequent resolution of her brain lesion and significant improvement in her spine disease. The second patient presented with left-sided weakness and a visual field deficit and underwent a partial resection of a right thalamic BRAF V600E-positive ganglioglioma. She began first-line therapy with dabrafenib with subsequent neurologic improvement and a decrease in T2 hyperintensity and resolution of tumor enhancement on MRI. These contrasting cases highlight the need to consider early dabrafenib therapy in patients with high-risk BRAF V600E-positive tumors as a means to prevent further neurologic injury.